18F-FLT PET Imaging in a Patient With Sarcoidosis With Cardiac Involvement. (May 2015) - Norikane, Takashi; Yamamoto, Yuka; Maeda, Yukito; Noma, Takahisa; Nishiyama, Yoshihiro
<x xml:space="preserve">Abstract</x> Abstract FDG PET has been proposed to play a role in the diagnosis and therapy monitoring of sarcoidosis including cardiac involvement. However, assessing inflammatory lesions in cardiac sarcoidosis using FDG can be challenging because the FDG accumulates in normal myocardium. We report a case of sarcoidosis with cardiac involvement that underwent 3′-deoxy-3′-18F-fluorothymidine (FLT) PET. FLT PET images demonstrated increased uptake in the lymph nodes and left ventricle. After immunosuppressive therapy, a follow-up PET scan showed disappearance of FLT uptake in the lymph nodes and left ventricle.